Відповідь:
Пояснення:
в) (2a+b)²/(2a+b) - 4ab/(2a+b)=(4a²+b²)/(2a+b)
г) 3(х-3)х/х(9-х²)+3(х+3)/х(9-х²)+2х²/х(9-х²)=(3х²-9х+3х+9+2х²)/х(9-х²)=(5х²-6х+9)/х(9-х²)
В) 2а+б- 4аб/2а+б=2а•(2а+б) •б•(2а+б) -4аб/ 2а+б =4а^2+2аб+2аб+б^2-4аб/2а+б=4а^2+0+б^2/2а+б = 4а^2+б^2/2а+б
Г)
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Відповідь:
Пояснення:
в) (2a+b)²/(2a+b) - 4ab/(2a+b)=(4a²+b²)/(2a+b)
г) 3(х-3)х/х(9-х²)+3(х+3)/х(9-х²)+2х²/х(9-х²)=(3х²-9х+3х+9+2х²)/х(9-х²)=(5х²-6х+9)/х(9-х²)
В) 2а+б- 4аб/2а+б=2а•(2а+б) •б•(2а+б) -4аб/ 2а+б =4а^2+2аб+2аб+б^2-4аб/2а+б=4а^2+0+б^2/2а+б = 4а^2+б^2/2а+б
Г)